2010
DOI: 10.1016/j.jhazmat.2009.08.148
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic decomposition of 4-t-octylphenol over NaBiO3 driven by visible light: Catalytic kinetics and corrosion products characterization

Abstract: The photocatalytic decomposition of 4-t-octylphenol (4-t-OP) by NaBiO(3) photocatalyst and the catalyst stability in aqueous solution were investigated systematically for the first time. The results showed that some parameters such as catalyst dosage, initial 4-t-OP concentration and pH value of the solution had great effects on the photocatalytic activity. The NaBiO(3) photocatalyst maintained considerable catalytic performance under visible light (lambda>400 nm) irradiation and exhibited a higher photocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(23 citation statements)
references
References 33 publications
2
20
1
Order By: Relevance
“…Similar to nitrate, the nitrite ions also inhibit the degradation of AY. Previously, it was reported that EDTA was a good scavenger for h + from the VB and caused a significant decrease the degradation of pollutants from aqueous solutions [41]. However, in this study EDTA is not suppressed Fig.…”
Section: Effect Of Interfering Ionscontrasting
confidence: 52%
“…Similar to nitrate, the nitrite ions also inhibit the degradation of AY. Previously, it was reported that EDTA was a good scavenger for h + from the VB and caused a significant decrease the degradation of pollutants from aqueous solutions [41]. However, in this study EDTA is not suppressed Fig.…”
Section: Effect Of Interfering Ionscontrasting
confidence: 52%
“…Apart from Bi (III) containing compounds, Bi (V) containing compounds have also been reported as active photocatalysts. [22][23][24][25][26] NaBiO 3 exhibits much higher activity compared to BiVO 4 and n-doped TiO 2 for the decomposition of methylene blue (MB) under visible light. The attractive performance of NaBiO 3 is ascribed to its band structure where the CB consists of hybridized Na (3s) and O (2p) orbitals that exhibit large dispersion with high mobility for photo-excited electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to TiO 2 photocatalyst, NaBiO 3 exhibited an extremely efficient photocatalytic performance (degradation rate is over 99%) towards AO under visible light irradiation. The excellent performance could be attributed to the hybridized sp orbital in the conduction band of NaBiO 3 (Na 3s and O 2p hybridized orbits), supporting a high mobility on the sp bands for the photo-excited electrons, which may lead to suppression of the recombination of electron-hole pair and a relatively higher photocatalytic activity of the material than that of other photocatalysts [14]. …”
Section: Effect Of Catalyst Dosagementioning
confidence: 83%
“…Their results show that NaBiO 3 presented an efficient degradation towards the organic compounds. The photocatalytic degradation of sodium pentachlorophenate (PCP-Na) and 4-t-octylphenol (4-t-OP) over NaBiO 3 under visible light irradiation was reported by Chang et al [13,14]. Their results show that PCP-Na and 4-t-OP in aqueous solutions can be efficiently decomposed in the NaBiO 3 /visible light process.…”
Section: Introductionmentioning
confidence: 95%